Folk Narratives of Balawarte in Uson, Masbate - Mark Philip C Paderan; Eda Mae Conde Buenvenida; Darwin Sabang Munez Cuyos; Giefe Terana (Journal of English Education and Linguistics, 2020)
Mystery, as viewed by the society, is usually stated by an outsider in a certain locality who sees unusual occurrence thus, series of inquiry is rolled down to seek for understanding of a phenomenon that cannot be answered by science hence, can be unlocked through the collective narratives that the folks treasured and continuously shared. These narratives form part of folklore in a society that is bound to vanishing when left undocumented. An hour travel from the heart of Masbate is where the small town Uson in which a Balawarte is found. This is a symbolic rock-sculpture of Mary on the seaside of the town of Uson but has created a lot of stories therein which form part to answer the mystery. This ignited the researchers to explore the significant narratives on this existing phenomenon. Through this, the researchers explored the historical and cultural significance of Balwarte in Uson. Also, the researchers inquired about the different narratives of it. The study is an ethnographic and folkloristic approach were used such as structured and unstructured interviews to gather the narratives. The narratives were transcribed and analyzed using Thematic Analysis to get the historical, cultural, and folkloristic contribution of it in society.